COVID-19 associated pulmonary aspergillosis (CAPA): An added potential burden on India's pre-existing fungal superinfection - Priyanka Mohan Lal; Aabiya Arif; Anmol Mohan; Sudhan Rackimuthu; Mohammad Mehedi Hasan; Zarmina Islam; Utkarsha Uday; Um-; Muhammad Taha Arshad Shaikh; Mohammad Yasir Essar (Elsevier, 2022)
The ongoing pandemic that initiated in Wuhan, China, has been an international public health emergency since January 2020. India has been battling a brutal COVID-19's second wave since April 2021. The healthcare system was struggling with a substantial increase in COVID-19 cases when the lack of necessary resources further aroused a major setback. Opportunistic fungal infections, specifically mucormycosis and candidiasis have become a pressing matter of concern. Recent cases of aspergillosis have also heightened public alarm. Hence, call for an immediate response to this public health crisis is the need of the hour by establishing countrywide surveillance, diagnostic, and management system, as well as public awareness to alleviate the burden of COVID-19 and fungal infections in India.